Consumption, (Dis) aggregate wealth and asset returns - Sousa, Ricardo M. (2005)
In this work, we analyze the importance of the disaggregation of wealth into its main components (financial and housing wealth). We show, from the consumerÂ´s intertemporal budget constraint, that the residuals of the trend relationship among consumption, financial wealth, housing wealth and labor income (summarized by the variable cday) should help to predict U.K. quarterly asset returns, and to provide better forecasts than a variable like cay from Lettau and Ludvigson (2001), which considers aggregate wealth instead. Using a sample for the U.K. for the period 1975:Q1 - 2003:Q4, we also find that: (i) financial wealth effects are significantly different from housing wealth effects; (ii) changes in financial wealth are mainly transitory, while changes in housing wealth are better understood as permanent; (iii) the relationship among consumption, (dis)aggregate wealth and labor income was relatively stable over time; (iv) consumption doesnÂ´t react asymmetrically to positive and negative financial (or housing) wealth shocks.